Inflation, price dispersion and market integration through the lens of a monetary search model - Sascha S. Becker; Dieter Nautz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
Monetary search theory implies that the real effects of inflation via its impact on price dispersion depend on the level of search costs and, thus, on the level of market integration. For less integrated markets, the inflation-price dispersion nexus is predicted to be asymmetrically V-shaped which results in an optimal inflation rate above zero. For highly integrated markets with low search costs, however, the impact of inflation on price dispersion should only be small. Using price data of the European Union member states, this paper is the first that tests and confirms these predictions of monetary search theory.
Keywords: C23; D40; E31; F40; 330; inflation; relative price variability; monetary search; market integration.; Inflation; Preisspanne; Relativer Preis; Marktintegration; Geldtheorie; Suchtheorie; Schätzung; EU-Binnenmarkt; EU-Staaten